Clinical practice patterns and ascertainment bias for cardiovascular events in a randomized trial: A survey of investigators in the BEST-CLI trial. (April 2021) - Albaghdadi, Mazen S; Young, Michael N; Chowdhury, Mohammed M.; Assmann, Susan; Hamza, Taye; Siami, Sandra; Villarreal, Maria; Strong, Michael; Menard, Matthew; Farber, Alik; Rosenfield, Kenneth
Ascertainment bias is a well-recognized source of bias in research, but few studies have systematically analyzed sources of ascertainment bias in randomized trials in which blinding is not possible and endpoint assessment is not protocolized. In the current study, we sought to evaluate differences in the clinical practice patterns of trial investigators with respect to bias in the ascertainment of pre-revascularization patient risk and the incidence of secondary endpoints post-revascularization. We conducted a cross-sectional survey of active investigators ( n = 936) from the Best Endovascular Versus Best Surgical Therapy for Patients with Critical Limb Ischemia (BEST-CLI) trial. The total survey response rate was 19.6% (183/936). Vascular surgeons were more likely than nonsurgical interventionalists to order tests for cardiac complications after both surgical bypass ( p < 0.001) and endovascular revascularization ( p = 0.038). Post-procedure, investigators were more likely to order additional testing for cardiac complications in open surgery versus endovascular cases (7% vs 16% never, 41% vs 65% rarely, 43% vs 17% sometimes, 9% vs 2% always, respectively; p < 0.0001). Significant variation in practice patterns exist in the pre- and post-procedure assessment of cardiac risk and events for patients with CLI undergoing revascularization. Variation in the ascertainment of risk and outcomes according to the type of revascularization procedure and physician specialty should be considered when interpreting the results of clinical studies, such as the BEST-CLI trial.ClinicalTrials.gov Identifier: NCT02060630